ANALISIS HALTE BUS TRANS SEMARANG (Studi Kasus Koridor I) - Dika Septavian Agita; Mudjiastuti Handajani; Ismiyati Ismiyati (Politeknik Negeri Semarang, 2021)
The construction of shelters that were not carried out simultaneously resulted in theconstruction of shelters along the Penggaron – Simpang Lima Semarang routeexperiencing differences even though they were in the same location. There is a needfor a review from the government regarding the capacity of the bus stops, thecondition of the shelters, the layout of the shelters and the distance of the bus stopsthat are still less than the standard. The lack of facilities owned by some TransSemarang bus stops and the distance from the bus stop users to the destination stopis still quite far, so people prefer to use private vehicles. From several analysisresults, there are several criteria that must be met for the placement of the positionand the distance of the bus stop that will affect the speed of the Trans Semarang busin determining the optimal location for a bus stop, one of the important factors isknowing the location of requests from BRT users where the location of the bus stoprequest is a source of generation. and the attraction of population movement and thelocation of the mode change before or after using the selected one.